Montserrat - Overseas Territory of the United Kingdom : Assessment of the Supervision and Regulation of the Financial Sector--Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses the observance of financial sector supervisory standards of Montserrat in the context of a Module 2 offshore financial center assessment. It reviews the extent to which the regulatory and supervisory arrangements for the offshore financial sector complied with internationally accepted standards in the offshore banking sector. The assessment also includes an evaluation of measures related to antimoney laundering and combating the financing of terrorism (AML/CFT) based on the AML/CFT methodology, which was endorsed by the Financial Action Task Force (FATF).